Some lessons from a life in food policy - Fan, Shenggen (Elsevier, 2019)
For 15 years, I had lived in a small village in southeastern China. We did not recognize malnutrition when we saw it, because to us it looked normal. We were all malnourished. Now, as I look back on my past decade as director general of the International Food Policy Research Institute, I can see how my own life illustrates the promise of food policy to change human lives. At the end of 2019, my term as director general comes to an end, and both IFPRI and I will begin new chapters. I take this opportunity to reflect on some of my experiences and lessons I have learned about how we can best exploit the promise of food policy to eradicate hunger and ensure food and nutrition security for all while we also protect our environment and planet. The global agri-food policy landscape has changed in many ways and have shown me that the world's agri-food systems are increasingly connected across national and regional boundaries, as well as linked to other sectors and forces. In this complex environment, effective food policy must be specific to the political, economic, geographic, social, and cultural environment where it takes place. Further, the complexity and interdependence of the world's agri-food systems mean that working alone is no longer an option. We have made important progress in working with different types of actors, such as private companies, civil society groups, and developing-country partners. We have learned another vital lesson for agricultural research and food policy that nutrition also affects people's health and well-being during the whole life cycle. As we better understand our complex and interconnected world, we have also learned that our work must increasingly be guided by considering not individual sectors and components, but entire food systems. I am incredibly proud of IFPRI's accomplishments over the years, only some of which are described here. Through their curiosity, insights, and hard work, IFPRI researchers have changed the food policy landscape, and I have been fortunate to play a supporting role. Of course, there will continue to be room for improvement and growth, and IFPRI faces challenges of its own. I have seen first-hand how the transformative power of food policy reform can save lives and improve well-being for millions. This is how I know that IFPRI and its partners worldwide can draw on the lessons of the past and a spirit of innovation for the future to achieve a world where hunger and malnutrition are only a memory.